"Flos campi et lilium convallium". Third Interpretation of the Lily in the Iconography of The Annunciation in Italian Trecento Art from Patristic and Theological Sources - Salvador González, José María (Eikón / Imago, 2014)
This paper (which complements two previous works of our authorship) proposes to interpret the bouquet of lilies in medieval images of The Annunciation in two essentially intertwined dogmatic meanings, related to Christology and Mariology. Contradicting conventional “explanations” of such flower in this Marian scene, we found our proposal in many and consistent testimony of some prestigious Church Fathers and medieval theologians, glossing the biblical sentence Ego sum flos campi et lilium convallium. Such lyrical expression is seen by those authors as a clear metaphor that identifies Christ, the incarnate Son of God, and that, as such, also refers to Mary, in whose virginal womb the Son of God’s incarnation is produced. Thus, based on the solid patristic and theological tradition on this biblical sentence, we dare to interpret the bouquet of lilies in paintings of the Annunciation (illustrated here by nine paintings of the Italian Trecento) as a double metaphor, which means both the supernatural human incarnation of God the Son and the virginal divine motherhood of Mary.